STRATEGI PEMASARAN USAHA PP. RIYADLUL JANNAH PACET MOJOKERTO PERSPEKTIF ILMU EKONOMI SYARIAH - M. Zidny Nafi' Hasbi; Muhammad Salman Al Farisi; Yutisa Tri Cahyani; Sigit Kusbiantoro (Jurnal Riset Entrepreneurship, 2021)
Marketing strategy is very important for a company, both small and large companies, especially when they want to develop the company and increase the number of consumers, as well as companies owned by PP. Riyadlul Jannah Pacet Mojokerto, there are many businesses owned by PP. Riyadlul Jannah Pacet Mojokerto includes the Meriah Kitchen Restaurant, M2M ,. Agri Bisnis, Rijan Mart, Franchese, Grilled Chicken Wong Solo, Shake Noodle Mang Uci Bandung, Quick Chicken, Organic Vegetable Mayur, Giant Super Market, Hero Super Market, Chicken Slaughterhouse, Rijan Mineral Water. Marketing strategy theories of many kinds, including: segmentation, Determining Target Markets, and Determining Market Position, marketing mix includes product creation, pricing, promotion, distribution, participants, processes and the physical environment. All of these strategies are theories of marketing strategies that are widely used by many companies. The research method used is a qualitative method which includes data sources both primary data and secondary data, data collection techniques namely observation, interviews, documentation, data analysis techniques namely editing and organizing, checking the validity of the data, and the research stage. All of this researchers use to find research results. Furthermore, the data contains an overview of the object of research and data obtained from interviews and other documents related to marketing, then a discussion contains the strategic strategies used to market the product and the constraints and solutions. The closing contains the conclusions from the discussion of the marketing strategy and the constraints and solutions, then also the suggestions given by the writer regarding the marketing strategy. merupakan sebuah ringkasan isi dari sebuah karya tulis ilmiah yang ditujukan untuk membantu seorang pembaca agar dapat dengan mudah dan cepat untuk melihat tujuan dari penulisannya